Smart parking systems by using Espresso Lite 2.0 - Abu, Mohd Azlan; Mohamad Jalil, Muhamad Farhan; Ramli, Aizat Faiz; Basarudin, Hafiz; Sulaiman, Mohamad Ismail; Suboh, Mohd Zubir; Romli, Fairuz Izzuddin (IEEE, 2017)
There are more and more vehicles on the road in every country, which have to be parked in spaces that are becoming increasingly packed. This is a big challenge especially for city planners, architects, and building owners. To meet this demand, the innovative and space saving-parking system is created. This is the new way of technology that can be applied to all users and it is more efficient than the previous parking systems. All buildings including hospitals, government building, shopping complex can access and apply this technology. This paper proposed a program that combined with the iOS system and connected through wireless connection. In addition, it will be connected to the mobile phones using this technology. Before the data can be displayed, the mobile phone has to be installed with BLINK's application that can be downloaded from the apple store. After this application is installed, then apps will show the available parking slot in the specific parking area. Any parking spaces can be assessed anywhere and anytime as long as users have internet connection to their smartphones. This paper proposed to develop the iOS apps that can show and update the parking spaces that are available and the hardware is designed by using ESPresso Lite 2.0 board.